Rates and Correlates of Incident Type 2 Diabetes Mellitus Among Persons Living With HIV-1 Infection - Ye, Yuanfan; Shrestha, Sadeep; Burkholder, Greer; Bansal, Anju; Erdmann, Nathaniel; Wiener, Howard; Tang, Jianming (Frontiers in Endocrinology, 2020)
The prevalence of various comorbidities continue to rise in aging persons living with HIV-1 infection (PLWH), and our study here aimed to assess the rates and correlates of incident type 2 diabetes mellitus (T2DM) in PLWH who receive combination antiretroviral therapy. Based on electronic health records, we examined patient demographics, body mass index (BMI), HIV-1-related outcomes, hepatitis C virus co-infection, common comorbidities (e.g. shingles and asthma), usage of protease inhibitors, and usage of statins as potential correlates for T2DM occurrence. Among 3,975 PLWH with ≥12 months of follow-up between January 1999 and March 2018, the overall rate of incident T2DM was 135 per 10,000 person-years, almost 2-fold higher than the rate reported for the general U.S. population. In multivariable models (354 T2DM patients and 3,617 control subjects), sex, BMI, nadir CD4+ T-cell count, HIV-1 viral load (VL) and duration of statin use were independent correlates of incident T2DM (adjusted P <0.05 for all), with clear consistency in several sensitivity analyses. The strongest associations (odds ratio/OR >2.0 and P <0.0001) were noted for: (i) statin use for ≥6 months (OR = 10.2), (ii) BMI ≥30 kg/m2 (OR = 3.4), and (iii) plasma VL ≥200 copies/ml (OR = 2.2). Their collective predictive value was substantial: the C-statistic for area under the receiver operating characteristics curve was 0.87 (95% CI = 0.84-0.90), showing close similarity for two major racial groups (C-statistic = 0.87 and 0.91 for African Americans and European Americans, respectively). Overall, these findings not only establish a promising algorithm for predicting incident T2DM in PLWH but also suggest that patients who are obese and use statins should require special consideration for T2DM diagnosis and prevention.